2021
DOI: 10.1001/jama.2021.7510
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response Teams as a Patient Safety Practice for Failure to Rescue

Abstract: This JAMA Performance Improvement article summarizes the AHRQ guideline on rapid response teams in its health care safety series, including whether rapid response teams decrease mortality or rates of cardiac arrest, if their use improves patient outcomes, and what barriers hinder their success in the hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…During the COVID-19 pandemic, some hospitals adjusted their RRS to deal with the incoming challenges, most commonly through increasing resources and implementation of protocol changes (15). However, the current research does not have sufficient evidence to draw a clear conclusion on whether the RRS and RRT can bring benefits, and the related research results were inconsistent (16). In a metaanalysis published in 2010, Chan et al analyzed data from 18 studies and found that the use of an RRT reduced the incidence of cardiopulmonary arrest in adults outside the intensive care unit (ICU) by 33.8% [risk ratio (RR) =0.66; 95% confidence interval (CI): 0.54-0.80], but did not reduce inpatient mortality (RR =0.96; 95% CI: 0.84-1.09); in children, it reduced the incidence of cardiopulmonary arrest outside the ICU by 37.7% (RR =0.62; 95% CI: 0.46-0.84), and also reduced hospital mortality in children by 21.4% (RR =0.79; 95% CI: 0.63-0.98) (17).…”
Section: Discussionmentioning
confidence: 79%
“…During the COVID-19 pandemic, some hospitals adjusted their RRS to deal with the incoming challenges, most commonly through increasing resources and implementation of protocol changes (15). However, the current research does not have sufficient evidence to draw a clear conclusion on whether the RRS and RRT can bring benefits, and the related research results were inconsistent (16). In a metaanalysis published in 2010, Chan et al analyzed data from 18 studies and found that the use of an RRT reduced the incidence of cardiopulmonary arrest in adults outside the intensive care unit (ICU) by 33.8% [risk ratio (RR) =0.66; 95% confidence interval (CI): 0.54-0.80], but did not reduce inpatient mortality (RR =0.96; 95% CI: 0.84-1.09); in children, it reduced the incidence of cardiopulmonary arrest outside the ICU by 37.7% (RR =0.62; 95% CI: 0.46-0.84), and also reduced hospital mortality in children by 21.4% (RR =0.79; 95% CI: 0.63-0.98) (17).…”
Section: Discussionmentioning
confidence: 79%
“…Knowledge of a patient's clinical status and usual behaviors gained through a full (head‐to‐toe) physical assessment is a key influence on a nurse's ability to recognize subtle changes in a patient's condition 1–4 . The importance of early recognition of deterioration before overt physiologic signs, such as vital sign changes, cannot be overstated given the link between unrecognized patient deterioration and serious adverse events 5–9 . However, physical assessment as practiced daily in contemporary nursing focuses more on vital signs than physical assessment; this is likely due to time restraints and a reliance on technology to determine patient's clinical status 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The importance of early recognition of deterioration before overt physiologic signs, such as vital sign changes, cannot be overstated given the link between unrecognized patient deterioration and serious adverse events. [5][6][7][8][9] However, physical assessment as practiced daily in contemporary nursing focuses more on vital signs than physical assessment; this is likely due to time restraints and a reliance on technology to determine patient's clinical status. 10 Often nurses face barriers to completing a physical assessment, including lack of time and unit culture, 11 ambiguity around who is responsible for physical assessments, reliance on technology, and lack of confidence in assessment skills.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although the reasons for a lack of obvious improvement in outcome with RRT implementation are incompletely understood, poor hospital safety culture, communication breakdown, and inadequate event detection mechanisms have been suggested. 1 In this issue of Anesthesia & Analgesia, Factora et al 4 review trends in inhospital mortality from 2005 to 2018 in noncardiac surgery patients at the Cleveland Clinic and their relationship to establishment of an RRT in 2009, a change to anesthesiology leadership of the RRT process in 2012, and further modifications in 2014. The authors hypothesized (1) that establishment of the RRT would be associated with reduction in mortality through better rescue of patients with acute physiologic decline and (2) that anesthesia leadership of the RRT would reduce mortality even further.…”
mentioning
confidence: 99%
“…3 Although the reasons for a lack of obvious improvement in outcome with RRT implementation are incompletely understood, poor hospital safety culture, communication breakdown, and inadequate event detection mechanisms have been suggested. 1…”
mentioning
confidence: 99%